The Development of Potential in Problem Solving of Production Staff in Glass Industry - Deewanichsakul, Songtham; Sramoon, Banleng; Wannaharnon, Arran (Princess of Naradhiwas University Journal, 2019)
The purposes of this research were to build the problem solving manual and training package operate and follow up the development of the potential in production problem solving of production staff in Glass Industry. The procedure of this research is divided into 3 steps. The results of the research wereas follows : 1) Build the problem solving manual and training package and 7 specialists to assess the appropriateness. The result of the evaluation was this training package was in highest level appropriate (X=4.57) 2) Conduct the training for 18 production staff in production line of Bangkok Glass Public Company Limited, Average achievement of the training was 87.50 percent. 3) Production staff operated problem solving process, the result of overall problem solving process was in high level (X= 4.00) and Follow up the problem solving results by asking supervisors chief. The result satisfaction was high level (X= 4.27)